Studying the Varying Impact of Working Memory, Attention and Pressure on Sports Performance in Presence of Physical Fitness: An Empirical Study - Jingchao Hu , Li Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The main aim of this study is to critically evaluate the influence of pressure, working memory and attention on the overall sports performance in the context of the sports sector in China. To fulfill that aim, game or job pressure is studied as an independent variable, sports performance as a dependent variable, while working memory capacity, working memory control and attention act as mediators within this research study. Authentic and first-hand sources of data collection were used for the purposes of this study wherein different online surveys were conducted to study the performance of Chinese athletes. For this purpose, relevant respondents i.e. athletes, coaches, management and related experienced stakeholders were considered for accurate data collection. After this, the confirmatory factor analysis and the structural equation modeling based authentic statistical tests have been performed whose outcomes justified the proposed hypothesis of this research. According to the SEM-based authentic outcomes, the game/ job pressure caused a negative significant impact on working memory capacity, working memory control, attention, and the overall sports performance of Chinese athletes. While, the mediators i.e. working memory capacity, working memory control and attention caused a positive significant impact on the sports performance within the context of this study. Overall, it’s an important source of information for the Chinese sports community, their coaches, trainers, decision-makers and other related ones to utilize its authentic data in their upcoming sports-related activities. Also, upcoming scholars can utilize this authentic data in their own research studies. This research also carries some contextual, theoretical, and methodological gaps that can be overcome by future researchers and scholars